Dioxin degradating capability and the identification of gene encode for dioxin dioxygenase of facultative anaerobic bacterial mixture setDN20 from toxic chemicals contaminated soils in Da Nang - Sang, Nguyen Thi; Minh, Nghiem Ngoc; Viet, Nguyen Quoc; Cam Ha, Dang Thi (Academia Journal of Biology, 2014)
The facultative bacterial mixture SETDN20 were isolated from 100 DNT biotreatment in toxic chemical contaminated site of Danang former military base. This bacterial mixture grews well in treated media that added soil extract. This soil extract not only contains 2,3,7,8-tetracloodibenzo-p-dioxin (2,3,7,8-TCDD) but also contain the other chlorinated congeners such as polychlorinated dibenzodioxin (PCDDs), polychlorinated dibenzofuran (PCDFs). The SETDN20 grews well at temperature 30oC in treated media which added soil extract and SETDN20 was able to remove 17.9% total toxicity. The diversity of bacterial mixture SETDN20 was studied base on the observer under TEM and DGGE (Denature gradient gel electrophoresis) techniques and showed that there are three diffirent strains. Results of encoding dioxin dioxygenase gene (with approximately 700 bp in lengh) and the deduced amino acid sequence analysis and comparison to those in the EMBL databases showed that enzyme was high homology ( 99% identity) to some representative of phenylpropionate dioxygienase. The preliminary results obtained indicate that SETDN20 may play certain role in dioxin degradation in facultative anaerobic condition which samely with condition of detoxification treatment by “active land fill” on the spot.